The Effect of Certified Teachers and Principal Leadership toward Teachers’ Performance - Heriana Hartiwi; Anna Yu Kozlova; Fitri Masitoh (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This study aimed at determining the influence certified teachers and principal leadership either partially or simultaneously toward teachers’ performance in primary school Palembang. The research was conducted in several public primary schools in Gadus, Palembang. The research method  was ex post facto with 125 certified teachers while the sample wer 56 respondents. The data were collected by using questionnaires and analyzed by using t-test and F-test. The results of this study concluded that there is significant influence of certified teachers and principal leadership either partially or simultaneously toword teachers’ performance of primary school in Palembang.